Hormonal regulation of delta opioid receptor immunoreactivity in interneurons and pyramidal cells in the rat hippocampus - Williams, Tanya J. (2011)
Clinical and preclinical studies indicate that women and men differ in relapse vulnerability to drug-seeking behavior during abstinence periods. As relapse is frequently triggered by exposure of the recovered addict to objects previously associated with drug use and the formation of these associations requires memory systems engaged by the hippocampal formation (HF), studies exploring ovarian hormone modulation of hippocampal function are warranted. Previous studies revealed that ovarian steroids alter endogenous opioid peptide levels and trafficking of mu opioid receptors in the HF, suggesting cooperative interaction between opioids and estrogens in modulating hippocampal excitability. However, whether ovarian steroids affect the levels or trafficking of delta opioid receptors (DORs) in the HF is unknown. Here, hippocampal sections of adult male and normal cycling female Sprague-Dawley rats were processed for quantitative immunoperoxidase light microscopy and dual label fluorescence or immunoelectron microscopy using antisera directed against the DOR and neuropeptide Y (NPY). Consistent with previous studies in males, DOR-immunoreactivity (-ir) localized to select interneurons and principal cells in the female HF. In comparison to males, females, regardless of estrous cycle phase, show reduced DOR-ir in the granule cell layer of the dentate gyrus and proestrus (high estrogen) females, in particular, display reduced DOR-ir in the CA1 pyramidal cell layer. Ultrastructural analysis of DOR-labeled profiles in CA1 revealed that while females generally show fewer DORs in the distal apical dendrites of pyramidal cells, proestrus females, in particular, exhibit DOR internalization and trafficking towards the soma. Dual label studies revealed that DORs are found in NPY-labeled interneurons in the hilus, CA3, and CA1. While DOR colocalization frequency in NPY-labeled neuron somata was similar between animals in the hilus, proestrus females had fewer NPY-labeled neurons that co-labeled with DOR in stratum oriens of CA1 and CA3 when compared to males. Ultrastructural analysis of NPY-labeled axon terminals within stratum radiatum of CA1 revealed that NPY-labeled axon terminals contain DORs that are frequently found at or near the plasma membrane. As no differences were noted by sex or estrous cycle phase, DOR activation on NPY-labeled axon terminals would inhibit GABA release probability equally in males and females. Taken together, these findings suggest that ovarian steroids can impact hippocampal function through direct effects on DOR levels and trafficking in principal cells and broad indirect effects through reductions in DOR-ir in NPY-labeled interneurons, particularly in CA1.